Resilience of primary healthcare professionals: a systematic review - Robertson, Helen D; Elliott, Alison M; Burton, Christopher; Iversen, Lisa; Murchie, Peter; Porteous, Terry; Matheson, Catriona (British journal of general practice, 2016)
Modern demands and challenges among healthcare professionals can be particularly stressful and resilience is increasingly necessary to maintain an effective, adaptable, and sustainable workforce. However, definitions of, and associations with, resilience have not been examined within the primary care context. To examine definitions and measures of resilience, identify characteristics and components, and synthesise current evidence about resilience in primary healthcare professionals. A systematic review was undertaken to identify studies relating to the primary care setting. Ovid(®), Embase(®), CINAHL, PsycINFO, and Scopus databases were searched in December 2014. Text selections and data extraction were conducted by paired reviewers working independently. Data were extracted on health professional resilience definitions and associated factors. Thirteen studies met the inclusion criteria: eight were quantitative, four qualitative, and one was an intervention study. Resilience, although multifaceted, was commonly defined as involving positive adaptation to adversity. Interactions were identified between personal growth and accomplishment in resilient physicians. Resilience, high persistence, high self-directedness, and low avoidance of challenges were strongly correlated; resilience had significant associations with traits supporting high function levels associated with demanding health professional roles. Current resilience measures do not allow for these different aspects in the primary care context. Health professional resilience is multifaceted, combining discrete personal traits alongside personal, social, and workplace features. A measure for health professional resilience should be developed and validated that may be used in future quantitative research to measure the effect of an intervention to promote it.